Development of aerobic fitness in young team sport athletes - Harrison, C. B.; Gill, N. D.; Kinugasa, T.; Kilding, A. E. (Sports Medicine, 2015)
The importance of a high level of aerobic fitness for team sport players is well known. Previous research suggests that aerobic fitness can be effectively increased in adults using traditional aerobic conditioning methods, including high-intensity interval and moderate-intensity continuous training, or more recent game-based conditioning that involves movement and skill-specific tasks, e.g. small-sided games. However, aerobic fitness training for youth team sport players has received limited attention and is likely to differ from that for adults due to changes in maturation. Given young athletes experience different rates of maturation and technical skill development, the most appropriate aerobic fitness training modes and loading parameters are likely to be specific to the developmental stage of a player. Therefore, we analysed studies that investigated exercise protocols to enhance aerobic fitness in young athletes, relative to growth and maturation, to determine current best practice and limitations. Findings were subsequently used to guide an evidence-based model for aerobic fitness development. During the sampling stage (exploration of multiple sports), regular participation in moderate-intensity aerobic fitness training, integrated into sport-specific drills, activities and skill-based games, is recommended. During the specialisation stage (increased commitment to a chosen sport), high-intensity small-sided games should be prioritised to provide the simultaneous development of aerobic fitness and technical skills. Once players enter the investment stage (pursuit of proficiency in a chosen sport), a combination of small-sided games and high-intensity interval training is recommended.